2015
DOI: 10.1038/am.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free growth of InAs/InxGa1−xAs coaxial nanorod heterostructures on graphene layers using molecular beam epitaxy

Abstract: We report the catalyst-free growth of InAs/In x Ga 1 − x As coaxial nanorod heterostructures on large-area graphene layers using molecular beam epitaxy and our investigation of the chemical composition and crystal structure of these heterostructures using electron microscopy. The graphene layers used as the substrate were prepared by chemical vapor deposition and transferred onto SiO 2 /Si substrates. InAs nanorods and their heterostructures were grown vertically on the graphene layers; electron microscopy ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
(37 reference statements)
0
11
0
1
Order By: Relevance
“…An intriguing potential substrate for epitaxial growth of semiconductors is graphene, the single-layer form of carbon, as it can not only act as an atomically thin crystalline growth template but also has outstanding functional properties when it comes to strength, flexibility, and electron and thermal conductivity. , Hybrid systems based on the growth of semiconductor nanocolumns on different graphitic substrates have been intensively studied in the past decade with the aim of developing new functionalities and higher efficiency optoelectronic devices as, for example, solar cells, photodetectors, light-emitting diodes (LEDs) and lasers. Such hybrid systems have been demonstrated for GaAs, InAs, InAsSb, In­(Ga)­As, , ZnO, , and GaN. With regards to the growth of GaN nanocolumns, different graphitic forms have been used as growth substrate, for instance, graphite, transferred chemical vapor deposition (CVD) graphene (single- and multilayer), and epitaxial graphene .…”
Section: Nanocolumn Growth and Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…An intriguing potential substrate for epitaxial growth of semiconductors is graphene, the single-layer form of carbon, as it can not only act as an atomically thin crystalline growth template but also has outstanding functional properties when it comes to strength, flexibility, and electron and thermal conductivity. , Hybrid systems based on the growth of semiconductor nanocolumns on different graphitic substrates have been intensively studied in the past decade with the aim of developing new functionalities and higher efficiency optoelectronic devices as, for example, solar cells, photodetectors, light-emitting diodes (LEDs) and lasers. Such hybrid systems have been demonstrated for GaAs, InAs, InAsSb, In­(Ga)­As, , ZnO, , and GaN. With regards to the growth of GaN nanocolumns, different graphitic forms have been used as growth substrate, for instance, graphite, transferred chemical vapor deposition (CVD) graphene (single- and multilayer), and epitaxial graphene .…”
Section: Nanocolumn Growth and Structural Characterizationmentioning
confidence: 99%
“…4,5 Hybrid systems based on the growth of semiconductor nanocolumns on different graphitic substrates have been intensively studied in the past decade with the aim of developing new functionalities and higher efficiency optoelectronic devices as, for example, solar cells, photodetectors, light-emitting diodes (LEDs) and lasers. Such hybrid systems have been demonstrated for GaAs, 6 InAs, 7−9 InAsSb, 10 In(Ga)As, 11,12 ZnO, 13,14 and GaN. With regards to the growth of GaN nanocolumns, different graphitic forms have been used as growth substrate, for instance, graphite, 15 transferred chemical vapor deposition (CVD) graphene (single-and multilayer), 16−25 and epitaxial graphene.…”
mentioning
confidence: 99%
“…Moreover, graphene is a low cost substrate that has high mechanical strength and flexibility, excellent electrical properties and optical transparency. The direct growth of semiconductor NWs on graphene has already been demonstrated, mainly using metal-organic chemical vapor deposition [23][24][25][26][27][28][29][30][31][32]. In particular, self-assisted van der Waals growth of InAs NWs on graphene was shown to be an alternative to that on Si/SiO 2 [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years Munshi et al showed that MBE can be used to obtain GaAs NWs on graphene [25,28]. Zhuang et al demonstrated In droplet-assisted MBE growth of InAs nanorods on mechanically exfoliated graphite flakes [31], and quite recently Tchoe et al obtained core/shell InAs/InGaAs coaxial nanorod heterostructures on graphene layers using MBE [32]. The development of a catalyst-free MBE growth method to produce ultrapure InAs NWs with controllable morphological and structural properties is of great importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation